2018
DOI: 10.1038/s41598-018-20533-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel non-periodic spoof surface plasmon polaritons with H-shaped cells and its application to high selectivity wideband bandpass filter

Abstract: In this paper, one kind of novel non-periodic spoof surface plasmon polaritons (SSPPs) with H-shaped cells is proposed. As we all know, the cutoff frequency exists inherently for the conventional comb-shaped SSPPs, which is a kind of periodic groove shape structures and fed by a conventional coplanar waveguide (CPW). In this work, instead of increasing the depth of all the grooves, two H-shaped cells are introduced to effectively reduce the cutoff frequency of the conventional comb-shaped SSPPs (about 12 GHz) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…A new kind of SSPP structure with periodic loading of T‐shape grooves is introduced in [15]. A comb‐shaped SSPP structure loaded with two H‐shaped cells in the centre forms a non‐periodic SSPP [16], and a highly selective wideband bandpass filter (BPF) is realized by using spiral‐shaped defected ground structure on coplanar waveguide (CPW). Owing to inimitable advantages such as high field confinement, slow‐wave characteristic and flexible planar structure, SSPPs has inspired a lot of research work in the design of microwave, millimetre‐wave and THz devices.…”
Section: Introductionmentioning
confidence: 99%
“…A new kind of SSPP structure with periodic loading of T‐shape grooves is introduced in [15]. A comb‐shaped SSPP structure loaded with two H‐shaped cells in the centre forms a non‐periodic SSPP [16], and a highly selective wideband bandpass filter (BPF) is realized by using spiral‐shaped defected ground structure on coplanar waveguide (CPW). Owing to inimitable advantages such as high field confinement, slow‐wave characteristic and flexible planar structure, SSPPs has inspired a lot of research work in the design of microwave, millimetre‐wave and THz devices.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to using SRRs and complementary SRRs in designing SSPPs filters, resonators with different configurations, for example, H-shaped resonators and complementary H-shaped slots have been utilized in a SSPP filter, so that complementary slots of the H-shaped periodic conductor units are embedded by multiple smaller H-shaped conductor strips in the middle 36 . In other proposed SSPPs filter configurations, a series of rectangular slots in the centre of metal strip 37 , a capacitive-coupled series SSPPs comprised of two H-shaped unit cells separated by a gap 38 , and two H-shaped cells in the center of non-periodic SSPPs fed by a CPW with defected ground planes 39 have been employed to design SSPPs band-stop filters. Furthermore, metamaterial particles are introduced in the vicinity of the ultrathin corrugated metallic strip for controlling frequency rejections of SSPPs 40 .…”
Section: Introductionmentioning
confidence: 99%
“…[12] In 2018, Gao et al proposed a highly selective metamaterial to be a broad bandpass filter using nonperiodic surface plasmon polariton. [13] In the meantime, Lee et al demonstrated MEMS-based Nomenclature SRR split-ring resonator MEMS micro-electro-mechanical system Qfactor quality factor THz terahertz IR infrared Si silicon GaAs gallium arsenide Ge germanium PDMS polydimethylsiloxane PEG polyethylenediformate ethylene glycol LC inductance-capacitance VO 2 vanadium dioxide CRR closed ring resonator PSM parabolic-shaped metamaterialparabolicshaped metamaterial LiNbO 3 lithium niobate FWHM full width at half maximum HEMT high electron mobility transistor metamaterials to assist the control of incident electromagnetic wave. [14] In 2019, the same research group (Lee et al) demonstrated two independent SRRs to form the double-cantilevers, which lifting height can be regulated by driving voltage.…”
Section: Introductionmentioning
confidence: 99%